The Influence of Job Satisfaction on Employee Engagement with Trust as a Moderation Variable in Employees in Private Education X Surabaya - Rachmawati, Annisa Mustika; Saptandari, Pinky; Setijaningrum, Erna (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Human Resources is one of the important keys for the organization to be able to achieve goals and develop. For this reason, it requires effective management of human resources to improve the competence and performance of these human resources by making sure that these human resources can feel engaged and have trust in their organization. This study aims to examine and analyze the effect of job satisfaction on employee engagement in non-lecturer employees of Private Higher Education Surabaya with trust as the moderator variable. This study used a quantitative approach with the dependent variable is employee engagement, independent variable is job satisfaction and the moderating variable is trust. Primary data were obtained from initial interviews and filing out closed questionnaires using a purposive sampling technique involving 156 respondents in non-faculty Administration work units/directorates. Data analysis technique are multiple linear analysis. The results of this study show that job satisfaction has a positive an significant impact on employee engagement, and there is an influence between job satisfaction on employee engagement administration employees at Private Higher Education X Surabaya with trust as a moderator variable.